A discussion about the rod position in the splitting tensile tests on hollow concrete blocks - Chávez Gómez, Jorge Humberto; Alvarez Pérez, José; Mesa Lavista, Milena; Fajardo San Miguel, Gerardo; Cavazos de Lira, Diego; González Alcorta, Ricardo (Multidisciplinary Digital Publishing Institute, 2023)
Different loading conditions cause different tensile stress patterns in masonry structures. Several studies related to masonry behavior use indirect tensile tests to obtain that value, where the splitting test from ASTM-C-1006 is usually employed. In this paper, an experimental analysis of the tensile strength of hollow concrete blocks is reported. Different locations of the rod from the ASTM-C-1006 splitting test were analyzed. The tensile strength was evaluated in four different ways, placing the rod: (1) in the transversal direction over the gross area, (2) in the transversal direction over the net area, (3) in the longitudinal direction, and (4) 200 mm from the central region of the block in the longitudinal direction. The obtained results were compared with the tensile strength values measured from the direct tensile test in the longitudinal direction. In addition, an axial compressive test was performed to characterize the blocks, and a discussion about the tensile/compression ratio is shown. The experimental results from the splitting tests show that for each configuration setup, the tensile stress is different. The main result was that the splitting test over the net area with the rod positioned in the longitudinal direction can overestimate the tensile strength by more than 21% of the one over the gross area.